Parallel Network Control Method on Auxiliary Power Supply System of Subway Train - Junjun SONG; Miaomiao DU; Wenyong GUO; Rushi LI; Hongxing ZHANG (机车电传动)
Aiming at the advantages and disadvantages of two kinds of power supply modes, i.e. extended power supply and grid power supply, the grid power supply mode was introduces, and the time-sharing start control algorithm of grid power supply of auxiliary converter, the control method of medium voltage contactor and the short circuit detection process were analyzed in detail.The application of the control algorithm in a metro train was stable, which indicated that the development of medium voltage AC grid power supply technology has been basically mature.